Process–Structure–Properties Relationships of Passivating, Electron‐Selective Contacts Formed by Atmospheric Pressure Chemical Vapor Deposition of Phosphorus‐Doped Polysilicon. Issue 5 (11th February 2022) - Mousumi, Jannatul Ferdous; Gregory, Geoffrey; Ganesan, Jeya Prakash; Nunez, Christian; Provancha, Kenneth; Seren, Sven; Zunft, Heiko; Jurca, Titel; Banerjee, Parag; Kar, Aravinda; Kumar, Ranganathan; Davis, Kristopher O.
Abstract : Herein, we investigate the process–structure–properties relationships of in situ phosphorus (P)‐doped polycrystalline silicon (poly‐Si) films by atmospheric pressure chemical vapor deposition (APCVD) for fabricating poly‐Si passivating, electron selective contacts. This high‐throughput in‐line APCVD technique enables to achieve a low‐cost, simple manufacturing process for crystalline silicon (c‐Si) solar cells featuring poly‐Si passivating contact by excluding the need for vacuum/plasma environment, and additional post‐deposition doping steps. A thin layer of this P‐doped poly‐Si is deposited on an ultrathin (1.5 nm) silicon oxide (SiO x ) coated c‐Si substrate to fabricate the passivating contact. This is followed by various post‐deposition treatments, including a high‐temperature annealing step and hydrogenation process. The poly‐Si films are characterized to achieve a better understanding of the impacts of deposition process conditions and post‐deposition treatments on the microstructure, electrical conductivity, passivation quality, and carrier selectivity of the contacts which assists to identify the optimal process conditions. In this work, the optimized annealing process with post‐hydrogenation yields passivating contact with a saturation current density ( J 0 ) of 3 fA cm −2 and an implied open‐circuit voltage ( iV OC ) of 712 mV on planar c‐Si wafer. Junction resistivity values ranging from 50 to 260 mΩ cm 2 are realized for the poly‐Si contacts processed in the optimal annealing condition. Abstract : Phosphorus (P) concentration and deposition temperature significantly control the microstructure, electrical properties, and passivation quality of oxide passivated in‐situ P‐doped poly‐Si contact fabricated by atmospheric pressure chemical vapor deposition process (APCVD). Post‐deposition annealing in optimal conditions with hydrogenation yields excellent APCVD poly‐Si passivating contact with saturation current density ( J 0 ) of 3 fA cm −2 and implied open‐circuit voltage ( iV OC ) of 712 mV.